"Press on regardless!" - The role of volitional control in the first year of higher education - Caroline Trautwein; Katrin Stolz (Forum Neue Medien in der Lehre Austria, 2015)
Students' motivation is an important predictor of study success and retention, but it declines severly during the first year in higher education. Despite this decline, about two thirds of students continue their studies. Thus, we explored the situations, in which students experience motivational decline, but apply strategies to maintain their motivation and academic goal striving in an interview study with 25 students. Our results indicate that students apply different volitional control strategies directed at their thoughts, their emotions, their motivation and their environment in order to maintain their learning and study motivation as well as their individual interest. 16.12.2015 | Caroline Trautwein & Katrin Stolz (Hamburg)